2009
DOI: 10.1179/135100009x466131
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol opposite effects on rat tissue lipoperoxidation: pro-oxidant during day-time and antioxidant at night

Abstract: We investigated the dosing-time dependency of acute resveratrol administration on lipoperoxidation level found in the heart, liver and kidney of male rats synchronized with a 12-h dark-light cycle. Resveratrol was administered by the i.p. route at the middle of the dark (6 h after dark onset, HADO) or light span (18 HADO) and thiobarbituric acid reactive species (TBARS) measured 4 h later at 10 and 22 HADO, respectively. Basal TBARS levels in the three organs were higher during the night span when compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 24 publications
2
49
0
1
Order By: Relevance
“…A dose-dependent anti-and pro-oxidant effect has been previously reported with other NA, both in vitro and in vivo experimental models (Cao et al, 1997;Gadacha et al, 2009;Yen et al, 2003), suggesting that the observed dual behavior is a general mechanism for NA. However, since antioxidant effects can vary depending on cell types and molecules used, the mechanisms involved in antioxidantmediated cellular responses are still largely unknown and need specific and detailed investigations.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…A dose-dependent anti-and pro-oxidant effect has been previously reported with other NA, both in vitro and in vivo experimental models (Cao et al, 1997;Gadacha et al, 2009;Yen et al, 2003), suggesting that the observed dual behavior is a general mechanism for NA. However, since antioxidant effects can vary depending on cell types and molecules used, the mechanisms involved in antioxidantmediated cellular responses are still largely unknown and need specific and detailed investigations.…”
Section: Resultsmentioning
confidence: 73%
“…Although this finding may appear controversial, if analyzed in association with the volume of literature concerning resveratrol, it has been reported that dosage and interaction with the redox state environment appear of primary importance, especially when precise redox modulation is needed to allow physiological function or to promote deleterious effects. For instance, resveratrol can work as a pro-oxidant under low oxidative conditions, while it becomes an antioxidant under strong oxidative conditions (Gadacha et al, 2009;Giordo et al, 2013). On the other hand, under normal oxidative conditions, the anti-and pro-oxidant behavior of resveratrol appears strictly related to its dosage, being antioxidant at low concentrations and pro-oxidant at higher ones Ladurner et al, 2014;Pasciu et al, 2010;Schilder et al, 2009).…”
Section: Resultsmentioning
confidence: 97%
“…This is despite the fact that there is no consensus as to its modes of action (Bhullar & Hubbard, 2015; Bitterman & Chung, 2015). In particular, RSV might act as an antioxidant, but other redox effects have also been documented (e.g., Miura et al ., 2000; Stivala et al ., 2001; Galati et al ., 2002; Ahmad et al ., 2003, 2005; Zheng et al ., 2006; de la Lastra & Villegas, 2007; Gadacha et al ., 2009; Queiroz et al ., 2009; Gueguen et al ., 2015). In addition, numerous distinct specific targets have been identified and characterized (reviewed in Bhullar & Hubbard, 2015; Bitterman & Chung, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A study revealed formation of superoxide (Ahmad, Clement, & Pervaiz, 2003). In the dark, AO properties prevail whereas under light exposure, oxidative effects are predominant (Gadacha, ben-Attia, Bonnfont et al, 2009). Another rationale exists for the pro-oxidant effects based on complex formation with heavier metals capable of ET (see Introduction).…”
Section: Resveratrol (Rsv)mentioning
confidence: 99%